Effect of pretreatment conditions on the chemical–structural characteristics of coconut and palm kernel shell: A potentially valuable precursor for eco-efficient activated carbon production - Lee, Chuan Li; Chin, K. L.; H’ng, Paik San; Rashid, Umer; Maminski, M.; Khoo, Pui San (Elsevier, 2021)
Non-renewable nature of commercial coal-based activated carbon has pushed researchers to look for sustainable alternatives which are inexpensive and abundantly available such as palm kernel shell (PKS) and coconut shell (CS). In this study, preparation of the lignocellulosic biomass using acid (HPO4), alkali (NaOH) and water pretreatment have been investigated. Pretreatment temperature and time were determined as the significant factors on the chemical–structural characteristics of CS and PKS. In addition, BET, SEM, FTIR, TGA were used to elucidate the development of PKS and CS and its capacity towards the adsorption of methylene blue and iodine. By varying the pretreatment conditions and process, it offers the possibility of modifying and controlling the porous texture of the biomass to prepare it as potential precursor for further physical thermal process during activated carbon production. The pretreated biomass results showed that the adsorption of methylene blue (14.35–16.92​ mg/g) and iodine value (20.14–23.86 mg/g) were significantly higher than non-treated biomass (methylene blue adsorption: 1.71–1.79 mg/g, iodine adsorption: 0.77–1.28 mg/g). Moreover, the results also revealed that pretreatment temperature and time have significantly affected the adsorbent properties of biomass. The pretreatment of biomass with HPO4 created a better development of porous structure. The highest surface area for CS (89.09 m2/g) and PKS (70.01 m2/g) were attained by using H PO4 at 80 °C for 2 h. The impregnation pretreatment simultaneously unclog existing pores from ash minerals while create new cracks and pores.